Bissu: Keistimewaan Gender dalam Tradisi Bugis - Titiek Suliyati (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
As one of many ethnics in Indonesian, Bugis ethnic posses much uniqness compared to other Indonesian ethnics. Bissu as one of Bugis traditions is gender spisification that does not exist either in man or woman. Indonesian society generally acknowledge man and woman gender. This is different from gender qualification in Bugis society. In Bugis society gender has five categories: Oroane is man either physically or its role in every day live; makkunrai is a woman either physically or its nature as woman; calalai is a woman behaves as a man; calabai is a man behaves as a woman. Bissu is a group does not belong to the four above genders. The performance of Bissu is very special because of its costume. This group wear neither man or woman costumes.Traditional Bugis society consider Bissu as combination of the four above gender. Not all Calalai or Calabai can become a Bissu. Being a Bissu is gods gift. Bugis society respect higly to Bissu, because Bissu has knowledge about tradition, family root, social life, traditional mystical cure and the life of gods. Bissu is able to communicate with the deaths and gods. Because Bisu is considered as a holy creature, they have an exlusive life. At present, the number and activities of Bissu is decreasing because of the changing of the government sytem: from monarchy to republic, the DI/TII rebellion in 1950, that wanted to abolish Bissu existence due to the abuse of Islamic law.